Transformasi Karya Gambar Anak Usia Dini Menjadi Buku sebagai Integrasi Pembelajaran Seni dan Literasi - Mufidah, Mufidah; Pamungkas, Joko (Absorbent Mind, 2026)
This study aims to describe the stages and strategies implemented by teachers in developing children’s drawings into a book in early childhood education. The study employed a qualitative approach design conducted at TK Masjid Syuhada Yogyakarta. The research subject was the teacher of the art and creativity center. Data were collected through in-depth interviews, observations, and documentation, and analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the process of transforming children’s drawings into a book involves five main stages: (1) introduction to basic literacy, (2) exploration of children’s ideas and experiences, (3) organization of artwork into a portfolio, (4) further development and creative exploration, and (5) publication of the artwork into a book. The teacher’s strategies at each stage are participatory, constructivist, and child-centered, while also incorporating scaffolding in technical aspects without limiting children’s creativity. The learning process not only produces aesthetically valuable works but also integrates art development with early literacy and character building, including independence, responsibility, and self-confidence. Furthermore, publishing the artwork in book form provides authentic learning experiences, allowing children to recognize the value of their work and its potential to be appreciated by others. Therefore, transforming children’s drawings into a book can serve as an effective integrative learning model to enhance creativity and literacy in early childhood education.